Machinability of FCD 500 ductile cast iron using coated carbide tool in dry machining condition - AG Jaharah; Mohd Nor Azmi Mohd Rodzi; Asma Abdul Rahman; Mohd Nizam Ab Rahman; CH Che Hassan (Springer Nature Switzerland AG, 2024)
Machining is the most important manufacturing process in these modern industries especially for producing automotive component. In this study, ductile cast iron grade FCD 500 was machined using carbide cutting tool in dry end milling condition. The end milling parameters used were cutting speed of 180 m/min, 210 m/min dan 260 m/min. The feed rate of 0.10 mm/tooth, 0.25 mm/tooth and 0.40 mm/tooth, and the depth of cut of 0.30 mm, 0.60 mm dan 0.90 mm. Orthogonal L9 array in Taguchi method was employed in to carry out experimental work. The results were analyzed using Analysis of Variance (ANOVA) to determine the effect of end milling parameters on the tool life, cutting force and surface roughness measured. From the analysis it was found that the depth of cut and feed rate are the most important parameter influencing the tool life. The optimal tool life was found at cutting speed of 180 m/min, feed rate of 0.10 mm/tooth and depth of cut of 0.30 mm. A good surface finish was obtained at cutting speed of 260 m/min, feed of 0.10 mm/tooth and depth of cut of 0.90 mm. Whereas, at cutting speed of 210 m/min, feed of 0.10 mm/tooth and depth of cut of 0.30 mm, the lowest cutting force was measured. Wear mechanism at the tool surface such as crater wear, cracking and chipping were observed. These optimum parameters obtained will help automotive industry to have a competitive machining operation from the economical and manufacturing perspective.